Reverse micelle extraction - Mohd. Setapar, Siti Hamidah (Penerbit UTM, 2007)
Reverse micelle is an alternative method to conventional separation and purification procedures due to their potential for large scale use (Ono et al., 1996; Naoe et al., 2004; Shen and Yu, 2007; Moore and Palepu, 2007), their potential application to continuous separation of biological substances (Zhang et al., 1999; Hong and Kuboi, 1999; Naoe et al., 2002; Noh and Imm, 2005; Juang et al., 2006; Majumdar and Mahapatra, 2007), the process similarities to liquid-liquid extraction (Naoe et al., 2004; Hasmann et al., 2007), and easy scale-up (Chang et al., 1997; Rodrigues et al., 1999; Kilikian et al., 2000; Mathew and Juang, 2007). Nishiki et al. (1998) showed that reverse micelle extraction is able to recover proteins with little denaturation because proteins can be hosted in a solubilised aqueous phase which is shielded from the organic solvent by surfactant molecules; solubilisation inside reverse micelle does not damage the native protein structure (Yu et al., 2003; Hetch and Peled, 2006). Therefore, in an ordinary liquid-liquid extraction, although it has been difficult to extract large bioactive molecules such as proteins, the limitation can be overcome by utilising a nanostructural molecular assembly like reverse micelle (Aires-Barros and Cabral, 1991; Ono et al., 1996).